2015
DOI: 10.1016/j.vetmic.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Salmonella enterica serovar Typhimurium phage type DT41 in Danish poultry production

Abstract: Salmonella enterica subspecies enterica serovar Typhimurium (S. Typhimurium) is one of the most prevalent serovars in Europe - where both poultry and poultry related products are common sources of human salmonellosis. Due to efficient control programs, the prevalence of S. Typhimurium in Danish poultry production is very low. Despite this, during the past decades there has been a reoccurring problem with infections with S. Typhimurium phage type DT41 in the Danish poultry production without identifying a clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…For all loci, apart from STTR9, there were some strains for which no amplicon was obtained, with the highest number of isolates for STTR10 (Table , Table S1). The discriminatory ability of the different MLVA loci corresponded well with previous investigations (Dimovski et al., ; Löfström, Hintzmann, Sørensen, & Baggesen, ; Wuyts et al., ), showing that STTR5, STTR6, and STTR10 were the loci with highest discriminatory index (DI) whereas a lower DI was observed for STTR3 and STTR9. STTR10 (plasmid borne) has in previous investigations been shown to be absent in many strains, thus being less useful for inclusion in the typing scheme.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…For all loci, apart from STTR9, there were some strains for which no amplicon was obtained, with the highest number of isolates for STTR10 (Table , Table S1). The discriminatory ability of the different MLVA loci corresponded well with previous investigations (Dimovski et al., ; Löfström, Hintzmann, Sørensen, & Baggesen, ; Wuyts et al., ), showing that STTR5, STTR6, and STTR10 were the loci with highest discriminatory index (DI) whereas a lower DI was observed for STTR3 and STTR9. STTR10 (plasmid borne) has in previous investigations been shown to be absent in many strains, thus being less useful for inclusion in the typing scheme.…”
Section: Resultssupporting
confidence: 89%
“…For all loci, apart from STTR9, there were some strains for which no amplicon was obtained, with the highest number of isolates for STTR10 (Table 2, Table S1). The discriminatory ability of the different MLVA loci corresponded well with previous investigations (Dimovski et al, 2014;Löfström, Hintzmann, Sørensen, & Baggesen, 2015;Wuyts et al, 2013), showing that STTR5, STTR6, and STTR10…”
Section: Resultssupporting
confidence: 88%
“…In this case, some breeding flocks related to this hatchery were infected with this phage type, but eggs from these flocks were also hatched in hatchery two, where no S. Typhimurium DT41 was isolated (data not shown). S. Typhimurium DT41 is normally associated with wild birds, particularly water fowl (Pennycott et al, 2006) but a spike in the prevalence of this serotype has been observed in broilers and broiler breeders in Denmark in recent years (Löfström et al, 2015). In this study, the tray wash area and waste/processing areas had the largest probability of being contaminated by Salmonella.…”
Section: Discussionmentioning
confidence: 59%
“…Contamination of chicken or chicken meat may occur throughout the whole production chain and some important risk factors for contamination at each stage of this process have been identified. The risk factors include inadequate cleaning and disinfection of broiler rearing houses, contamination of feed, and chicken production process; these factors can be a significant source of pathogen contamination between carcasses [5]. To our knowledge, S. enterica always exists in the alimentary tract and reproductive system of carrier chickens.…”
Section: Introductionmentioning
confidence: 99%